Die illuminierten Handschriften der Universitätsbibliothek Graz 1225-1300 - Schuller-Juckes, Michaela (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
The present volume is the result of a comprehensive investigation of 86 illuminated manuscripts and fragments that are now in the University Library in Graz. Produced between 1225 and 1300, the works almost all came to Graz from monasteries in Styria, Carinthia, and Slovenia, where they were held until the secularizations of the late 18th century.Manuscripts are among the most multifaceted forms of evidence from the Middle Ages, providing invaluable information on the time of their creation and on later periods. The present volume is the result of a comprehensive investigation of 86 illuminated manuscripts and fragments that are now in the University Library in Graz. Produced between 1225 and 1300, the works almost all came to Graz from monasteries in Styria, Carinthia, and Slovenia, where they were held until the secularizations of the late 18th century. The volume approaches this material from an art-historical perspective and sets it within its historical, cultural, and intellectual contexts. Stylistic analysis of the illuminations shows that only a relatively small proportion of the works was made locally, and that most of the manuscripts were imports from major centres of European book production - such as Bologna, Paris, or South France.